2014
DOI: 10.1666/13035
|View full text |Cite
|
Sign up to set email alerts
|

Controls on niche stability in geologic time: congruent responses to biotic and abiotic environmental changes among Cincinnatian (Late Ordovician) marine invertebrates

Abstract: The set of environmental conditions under which a taxon can survive and maintain viable populations, known as the ecological niche, is a fundamental determinant of a taxon's distribution. Because of the central importance of ecological niches, they have been assumed to remain relatively stable during intervals of morphological stasis. However, the assumption of niche stability has rarely been tested directly with fossil data spanning multiple temporal intervals. Thus, the conditions under which this assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 92 publications
1
33
0
Order By: Relevance
“… Summary of the weighted percent geographic overlap and environmental parameter similarity data through time. Patterns are congruent between the species‐level brachiopod data of Malizia and Stigall () and the cross‐faunal genus‐level data of Brame and Stigall (). The geographic overlap percentage declines significantly between the pre‐invasion and invasion intervals, whereas environmental parameter similarity statistically increases between the pre‐invasion and invasion intervals.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“… Summary of the weighted percent geographic overlap and environmental parameter similarity data through time. Patterns are congruent between the species‐level brachiopod data of Malizia and Stigall () and the cross‐faunal genus‐level data of Brame and Stigall (). The geographic overlap percentage declines significantly between the pre‐invasion and invasion intervals, whereas environmental parameter similarity statistically increases between the pre‐invasion and invasion intervals.…”
Section: Resultsmentioning
confidence: 57%
“…Combined, the analyses of Malizia and Stigall ()and Brame and Stigall () generated 111 niche models with an average AUC value of 0.80 (range 0.70 to 1.0). Although critiques of AUC as an accuracy measure have been raised (Peterson et al , Jiménez‐Valverde ), it remains a widely reported non‐threshold based metric, and the recovered values indicate good model fit to the data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Invasive taxa also included members of all trophic levels from pelagic predators to sessile benthos. The introduction of these new taxa caused a fundamental rearrangement of the community structure which had been stable for nearly 5 million years before the invasion (Patzkowsky & Holland 2007) and resulted in niche evolution among both native and incumbent species (Brame & Stigall 2014). …”
Section: Introductionmentioning
confidence: 99%